The Mediating Effect of ESG Performance on Board Structure and Financial Performance: Evidence of Indonesia - Ihbal, Ahmad; Ifada, Luluk Muhimatul (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024), 2024)
This study offers fresh data on the significance of corporate location in CSR reporting from nine developing nations, together with a review of the environment's present status and how eco-friendly behaviors and attitudes might preserve the planet. The Bloomberg database was used to gather environmental, social, and governance score data for the years 2013 through 2020. This study concludes some findings. First, independent members have an effect on the company's financial success. Second, independent boards do a lot of damage to ESG. The third thing is that the ESG may lessen the effect that independent members have on financial performance. The findings of this study will benefit any country where sustainable green practices are uncommon and the ecosystem deteriorates on a daily basis. Keywords : ESG performance, board structure and financial performance